2017
DOI: 10.18632/oncotarget.16323
|View full text |Cite
|
Sign up to set email alerts
|

Histone hypoacetylation contributes to CXCL12 downregulation in colon cancer: impact on tumor growth and cell migration

Abstract: CXCL12 has been shown to be involved in colon cancer metastasis, but its expression level and molecular mechanisms regulating its expression remain controversial. We thus evaluated CXCL12 expression in a large cohort of colon adenomas and carcinomas, investigated for an epigenetic mechanism controlling its expression and evaluated the impact of CXCL12 levels on cell migration and tumor growth. CXCL12 expression was measured in human colon adenomas and carcinomas with transcriptome array and RT-qPCR. The promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…On the other hand, the acetylation state of histone assembly regulated by histone acetyltransferase and deacetylase is known to alter CXCL12 transcription in osteoblasts and synovial fibroblasts 3638 . PCAF signaling is found to regulate the acetylation status of CXCL12 promoter 39 and osteogenic differentiation of mesenchymal stem cell cultures 40 . Our study further uncovered a noncanonical pathway that miR-29a inhibition of PCAF interfered with CXCL12 expression through H3K27 hypoacetylation and thus downregulated the H3K27ac occupancy in CXCL12 promoter in osteoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the acetylation state of histone assembly regulated by histone acetyltransferase and deacetylase is known to alter CXCL12 transcription in osteoblasts and synovial fibroblasts 3638 . PCAF signaling is found to regulate the acetylation status of CXCL12 promoter 39 and osteogenic differentiation of mesenchymal stem cell cultures 40 . Our study further uncovered a noncanonical pathway that miR-29a inhibition of PCAF interfered with CXCL12 expression through H3K27 hypoacetylation and thus downregulated the H3K27ac occupancy in CXCL12 promoter in osteoblast cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Class I HDAC inhibition using apicidin decreased its expression in pulmonary fibroblasts, demonstrating that class I HDACs induces CXCL12 expression [ 66 ]. However, in colon cancer cells, Romain et al observed that non-specific HDAC inhibition by vorinostat, valproic acid, butyrate increased CXCL12 expression, which was otherwise decreased in both MSI and MSS colon cancer tumors, warranting more studies on the roles of specific HDACs on CXCL12 expression [ 106 ].…”
Section: Chemokines Hdacs and Hdac Inhibitorsmentioning
confidence: 99%
“…Colon cancer is a leading cause of cancer deaths in the world and has been considered to arise from genetic alterations in genes encoding factors that help control cell growth and proliferation [ 12 , 13 ]. However, accumulating evidence indicates that epigenetic alterations generated by dysregulation of epigenetic modifiers play pivotal roles in the initiation, promotion, and progression of colon cancer [ 14 , 15 , 16 , 17 ]. Especially, histone modification is increasingly recognized as an essential process to control oncogenic transcription program and influence the occurrence and development of colon cancer [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%